(untitled) (Ius Novum, 2023)
The article is aimed at examining the admissibility of reopening cassation and reopening proceedings concluded with a decision to dismiss the extraordinary appeal measure. To this end, the article explores provisions on proceedings reopening (Articles 540 and 542 § 3 CCP), with particular focus on the term ‘court proceedings concluded with a final decision’ used by the legislator, and juxtaposes this with provisions on cassation appeal (concerning terms used in Article 521 of the Code of Criminal Procedure – ‘a final decision concluding court proceedings’ and ‘a final court decision concluding the proceedings’, and on prohibition of the so-called super-cassation, which has not been transferred to the institution of reopening of the proceedings). The author also analyses Supreme Court practice over the last twenty-odd years and reflects on historical changes to criminal procedure at the turn of the 21th century with regard to the institutions of annulment of court decisions and reopening of the proceedings.